Increased Risks at Sea? Global Shipping Downturn and Maritime Security - Bateman, Sam (2016)
International shipping has been severely affected by the global economic recession. Cost-cutting in the industry could affect maritime security with some diminution of the maritime security measures introduced post 9/11 when the industry was booming.